ANALISIS YURIDIS PERMOHONAN IZIN PENYELENGGARAAN RADIO PADA FREKUENSI 99,5 MEGAHERTZ (PERKARA TATA USAHA NEGARA NOMOR 86/G/2010/PTUN-MEDAN) - Tri Kurniawan; Pendastaren Tarigan; Suhaidi Suhaidi; Faisal Akbar (USU LAW JOURNAL, 2015)
ABSTRACT   Radio is a means of communication that does not use cable as its medium, but uses electromagnetic waves to transmit voice. The use of radio frequency spectrum in the manner intended, and should not interfere with each other as the nature of the radio frequency spectrum can propagate in any direction without knowing the limits of the country, therefore, its use should require a permit from the Government. Concluded, first, setting the organization of broadcasting about granting permission to use the radio frequency spectrum in Indonesia are required for every person who, either legal entities of government, private and foreign in Indonesia, radio broadcasting must obtain permission from the Government through the MCIT.  Secondly, the principles of good governance Government associated with broadcasting license application filed by PT. RPLN are not implemented optimally and wisely, especially the Minister of Communication and Head of the Institute of Radio Frequency Spectrum Monitor Class II Medan. Third, the basic consideration of the judge's decision to cancel the Minister of Communication on radio broadcasting license application filed by PT. RPLN legally well-founded based on a consideration of the principles or the principles of good governance and has in the law normative.